O Núcleo genuíno lateral dorsal do tálamo do sagüi (callithrix jacchus): Pprojeção retiniana, caracterização citoarquitetônica e neuroquimica da principal estação visual primária. - Borda, Janaina Siqueira (2009)
The thalamus plays an important role in the sensorial processing information, in this particular case, the visual information. Several neuronal groups have been characterized as conductors and processors of important sensorial information to the cerebral cortex. The lateral geniculate complex is one to them, and appears as a group very studied once it is responsible, in almost all totality, for the processing of visual information. Among the nuclei that constitute the lateral geniculate complex we highlight the dorsal lateral geniculate nucleus of the thalamus (DLG), the main thalamic relay for the visual information. This nucleus is located rostral and lateral to medial geniculate nucleus and ventral to thalamic pulvinar nucleus in most of the mammals. In the primates humans and non-humans, it presents as a laminate structure, arranged in layers, when observed in coronal sections. The objective of this work was to do a mapping of the retinal projections and a citoarchictetonic and neurochemical characterization of DLG in the marmoset (Callithrix jacchus), a New World primate. The retinal projections were traced by anterograde transport of subunit b of cholera toxin (CTb), the citoarchicteture was described by Nissl method, and to neurochemical characterization immunohistochemicals technical were used to examine the main neurotransmitters and neuroatives substances present in this neural center. In DGL of marmoset thalamus, in coronal sections labeled by Nissl method, was possible to visualize the division of this nucleus in four layers divided in two portions: magnocellular and parvocellular. The retinal projections were present being visualized fibers and terminals immunorreactives to CTb (IR-CTb) in the DLG ipsilateral and contralateral. And through the immunohistochemicals techniques was observed that DLG contain cells, fibers and/or terminals immunoreactives against neuronal nuclear protein, subunits of AMPA 15 glutamate receptors (GluR1, GluR2/3, GluR4), choline acetyltransferase, serotonin, glutamic acid decarboxylase, binding calcium proteins (calbindin, parvalbumin and calretinin), vasopressin, vasoactive intestinal polypeptide, and an astrocyte protein, glial fibrillary acidic protein.